2021
DOI: 10.14738/assrj.88.10673
|View full text |Cite
|
Sign up to set email alerts
|

Training of prosocial skills to migrant groups through serious games

Abstract: Due to forced migration migrants, asylum seekers and refugees finding themselves in a new cultural environment and trying to build a new life, they need to feel affiliated, to achieve peer acceptance among natives and diverse migrant groups. Such affiliation needs can be achieved by tailored training interventions aiming to promote the development of prosocial skills of cultural diverse groups, as alternative actions to facilitate better migrants’/asylum seekers/refugees’ integration into the host society. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Building on this, research on the antecedents of prosocial behaviour has illustrated critical motivational (Hepach and Warneken, 2018;Paulus, 2018), emotional (Buchanan and Preston, 2014), cognitive factors of prosocial decision-making (Will and Güroğlu, 2016), and personality-related aspects (Zhao et al, 2016;Heilman and Kusev, 2020) influencing the propensity to act prosocially. Studies have outlined the malleable nature of prosocial behaviour, advocating for several training approaches to encourage the development of prosocial skills (Böckler et al, 2018;Paulus, 2018;Tountopoulou et al, 2021). Experiments with economic games and theoretical frameworks in controlled settings have shown that factors such as communication (Burton-Chellew and West, 2013;Caviola and Faulmüller, 2014;Zhao et al, 2016), reciprocity (Allidina et al, 2019;Hsieh et al, 2023), reputation and reward (Hauert, 2010;Wang et al, 2012), as well as time constraints (Haley and Fessler, 2005;Kümmerli et al, 2010;Yamagishi et al, 2017), can significantly impact prosocial actions.…”
Section: Introductionmentioning
confidence: 99%
“…Building on this, research on the antecedents of prosocial behaviour has illustrated critical motivational (Hepach and Warneken, 2018;Paulus, 2018), emotional (Buchanan and Preston, 2014), cognitive factors of prosocial decision-making (Will and Güroğlu, 2016), and personality-related aspects (Zhao et al, 2016;Heilman and Kusev, 2020) influencing the propensity to act prosocially. Studies have outlined the malleable nature of prosocial behaviour, advocating for several training approaches to encourage the development of prosocial skills (Böckler et al, 2018;Paulus, 2018;Tountopoulou et al, 2021). Experiments with economic games and theoretical frameworks in controlled settings have shown that factors such as communication (Burton-Chellew and West, 2013;Caviola and Faulmüller, 2014;Zhao et al, 2016), reciprocity (Allidina et al, 2019;Hsieh et al, 2023), reputation and reward (Hauert, 2010;Wang et al, 2012), as well as time constraints (Haley and Fessler, 2005;Kümmerli et al, 2010;Yamagishi et al, 2017), can significantly impact prosocial actions.…”
Section: Introductionmentioning
confidence: 99%